Relationship between problem solving ability in physics and computational thinking skills - Ihsan Walimudin; Iman Nurzaman; Lasmita Sari (Institut Pendidikan Indonesia Garut, 2023)
The rapid development of technology today does not only require problem solving skills, other thinking skills such as computational thinking skills are needed in solving complex problems. This study aims to investigate the relationship between problem solving abilities in physics, especially vibrations and waves, and computational thinking skills. This study uses a correlation research design in which the relationship between two variables of problem-solving ability and computational thinking is observed. By using data from 21 eighth grade junior high school students who had participated in wave learning, it was found that the correlation between the two variables was in the moderate category. These data indicate that problem solving abilities contribute to students' computational thinking skills. Discussion of the results of this study will be discussed in more detail in this article.